2002
DOI: 10.1289/ehp.02110331
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for induction of oxidative stress caused by chronic exposure of Chinese residents to arsenic contained in drinking water.

Abstract: Exposure of experimental animals or cultured cells to arsenic induces oxidative stress, but, to date, no examination of this phenomenon in humans has been reported. In this study we conducted a cross-sectional study in Wuyuan, Inner Mongolia, China, to explore the relationship between chronic arsenic exposure from drinking water and oxidative stress in humans. Thirty-three inhabitants who had been drinking tube-well water with high concentrations of inorganic arsenic (mean value = 0.41 mg/L) for about 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
4
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(158 citation statements)
references
References 56 publications
9
143
4
2
Order By: Relevance
“…Arsenic is a human carcinogen (i.e., lung, skin, bladder, and liver; [Wickre et al, 2004;Yoshida et al, 2004] and populations in China have been shown to be exposed via drinking water and food consumption [Pi et al, 2002;Liu et al, 2003]. Toxic forms of arsenic include inorganic species (As 3+ and As 5+ ) as well as monomethylarsenite whereas arsenobetaines which are prevalent in seafood are considered benign [Shaw et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is a human carcinogen (i.e., lung, skin, bladder, and liver; [Wickre et al, 2004;Yoshida et al, 2004] and populations in China have been shown to be exposed via drinking water and food consumption [Pi et al, 2002;Liu et al, 2003]. Toxic forms of arsenic include inorganic species (As 3+ and As 5+ ) as well as monomethylarsenite whereas arsenobetaines which are prevalent in seafood are considered benign [Shaw et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitation of total iAs and trivalent arsenite [iAs(III)] in water and total iAs, MMA, DMA and trimethylarsenic (TMA) in urine were performed as reported previously (Yamauchi and Yamamura, 1984;Pi et al, 2002). Briefly, 0.20 ml urine samples were transferred into 20 ml polypropylene test tubes and after the addition of 0.80 ml 2 M sodium hydroxide to the sample, the mixture was heated at 951C for 3 h. The treated urine sample and the tube-well water sample were diluted to make a 2 ml sample.…”
Section: Analysis Of Arsenic In Urine and Tube-well Watermentioning
confidence: 99%
“…One Taiwanese study reported that ingestion of arsenic-contaminated well water may cause deleterious effects by increasing the level of reactive oxidants and decreasing the level of antioxidant capacity in the plasma of affected individuals (Wu et al, 2001). Another study reported that chronic exposure to arsenic in drinking water in humans results in induction of oxidative stress, as indicated by a reduction in nonprotein sulfydryl and an increase in lipid peroxides (Pi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, arsenic alone does not appear to induce skin cancer in these mouse models [2][3][4], suggesting events associated with arsenic-induced dermal carcinogenesis may be distinct from other target tissues. Accumulating evidence suggests that oxidative stress occurs in response to arsenic exposure [5,6] and may be one factor in dermal arsenic carcinogenesis. Indeed, evidence of arsenic-induced oxidative DNA damage has been observed in cells [7][8][9][10][11][12], in rodents [13] and in humans [14].…”
Section: Introductionmentioning
confidence: 99%